Strategic Approaches to Sustain Vannamei Shrimp Cultivation in Linduk, Banten - Prabawanti, Benedicta Evienia; Natarina, Angelika (Business Review and Case Studies, 2025)
Background: With the development of various techniques, aquaculture has played an important role in Indonesia's economic growth. Cultivation of vannamei shrimp is one of the most popular aquaculture practices. Vannamei shrimp is an export commodity, with significant results. The Linduk Aquaculture Pond in Banten Province is an example of this industry's contribution by providing economic benefits to the local community. Linduk was chosen as the research site because it is known as one of the aquaculture centers in Banten, supported by geographical and ecological conditions such as the availability of extensive pond land, water quality suitable for shrimp cultivation, and local community support for the fisheries sector. Furthermore, it is located close to the domestic market, facilitating distribution access to export markets through ports in Banten. Furthermore, several challenges, including limited capital, climate variability, seed quality, high operational costs, and management inefficiencies hamper optimal business performance.Purpose: This study aimed to identify and analyze business strategies for maintaining and increasing the productivity and growth of Linduk Aquaculture Ponds in Banten Province.Design/Methodology/Approach: This study involved two key internal stakeholders (the business owner and field coordinator), three customers, and three competitors as informants to provide comprehensive insights into the operational, market, and competitive dynamics of the Linduk shrimp aquaculture business.This study uses a qualitative approach, which integrates strategic management tools. The internal and external environments were analyzed using IFE, EFE, IE, SWOT, and QSPM matrices to produce actionable strategies.Findings/Results: The IE matrix shows that the business is in a "hold and maintain" position. The “hold and maintain” position in the IE matrix indicates that the business is currently stable and performing adequately, requiring strategies focused on sustaining existing market share and operational efficiency. Five alternative strategies were derived from the SWOT analysis, with QSPM identifying priority strategies to optimize shrimp growth and production.Conclusion: Strategic recommendations focus on maintaining business productivity by addressing the identified challenges and ensuring long-term growth and sustainability in the aquaculture sector.     Originality/value (State of the art): Previous studies have largely examined the common challenges in aquaculture, such as climate variability, seed quality, and operational costs. They have not specifically focused on formulating actionable strategies utilizing robust analytical frameworks such as the IFE, EFE, IE, SWOT, and QSPM matrices. This study addresses this gap by systematically identifying crucial internal and external factors, prioritizing context-specific strategies for local aquaculture enterprises, and offering a comprehensive roadmap for improving productivity, competitiveness, and sustainability in the Indonesian aquaculture industry.Keywords: aquaculture business, business strategy, competitiveness, sustainability, SWOT Analysis